2022
DOI: 10.1063/5.0073515
|View full text |Cite
|
Sign up to set email alerts
|

Breakdown characteristics of deep-ultraviolet Al0.6Ga0.4N p-i-n avalanche photodiodes

Abstract: A top-illuminated deep-ultraviolet Al0.6Ga0.4N p-i-n avalanche photodiode (APD) structure was designed and grown by metalorganic chemical vapor deposition on an AlN bulk substrate and on two different quality AlN/sapphire templates, and APDs were fabricated and tested. The APD devices with a circular diameter of 20  μm have demonstrated a distinctive reverse-bias breakdown behavior. The reverse breakdown voltage of the APDs is approximately −140 V, which corresponds to a breakdown electric field of 6–6.2 MV/cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The crystal quality of AlGaN grown on a bulk AlN substrate is intrinsically expected to be good because they both have the same crystallographic symmetry of wurtzite. Therefore, the use of the bulk AlN substrate during the photodetectors manufacturing is worth investigation [19][20][21][22][23][24][25] . For example, Jeong et al reported topilluminated Al 0.6 Ga 0.4 N p-i-n SBPDs grown on an AlN bulk substrate and on another two types of AlN templates with different quality [19] .…”
Section: Bulk Aln Templatementioning
confidence: 99%
See 1 more Smart Citation
“…The crystal quality of AlGaN grown on a bulk AlN substrate is intrinsically expected to be good because they both have the same crystallographic symmetry of wurtzite. Therefore, the use of the bulk AlN substrate during the photodetectors manufacturing is worth investigation [19][20][21][22][23][24][25] . For example, Jeong et al reported topilluminated Al 0.6 Ga 0.4 N p-i-n SBPDs grown on an AlN bulk substrate and on another two types of AlN templates with different quality [19] .…”
Section: Bulk Aln Templatementioning
confidence: 99%
“…Therefore, the use of the bulk AlN substrate during the photodetectors manufacturing is worth investigation [19][20][21][22][23][24][25] . For example, Jeong et al reported topilluminated Al 0.6 Ga 0.4 N p-i-n SBPDs grown on an AlN bulk substrate and on another two types of AlN templates with different quality [19] . They found that the peak of the AlGaN SBPD grown on the AlN bulk substrate has a narrower linewidth compared to those of the AlGaN SBPDs grown on the AlN/sapphire templates in X-ray diffraction-based reciprocal space mapping.…”
Section: Bulk Aln Templatementioning
confidence: 99%
“…SBUV light is usually very weak, making high gain and low dark current crucial for the detection. AlGaN SBUV detectors with internal gain, such as photoconductors and avalanche photodiodes (APDs), have been extensively studied. However, the photoconductors typically exhibit slow speed and high dark current due to the defect trapping effect. , Besides, although the APDs can achieve high gain, low dark current, and fast speed, the requirement of high-quality materials, high-efficient p-doping, high operating bias, and complex driving circuit limits their application. , …”
Section: Introductionmentioning
confidence: 99%